Early variation of 18-fluorine-labelled fluorodeoxyglucose PET-derived parameters after chemoradiotherapy as predictors of survival in locally advanced pancreatic carcinoma patients. Issue 10 (October 2019) - Incerti, Elena; Vanoli, Emilia G.; Broggi, Sara; Gumina, Calogero; Passoni, Paolo; Slim, Najla; Fiorino, Claudio; Reni, Michele; Mapelli, Paola; Cattaneo, Mauro; Zanon, Silvia; Calandrino, Riccardo; et al.
Abstract : Objective: To investigate if early variation of PET-derived parameters after concomitant chemoradiotherapy (CRT) predicts overall survival (OS), local relapse free survival (LRFS), distant relapse free survival (DRFS) and progression free survival (PFS) in locally advanced pancreatic cancer (LAPC) patients. Methods: Fifty-two LAPC patients (median age: 61 years; range: 35–85) with available FDG PET/CT before and after RT (2–6 months, median: 2) were enrolled from May 2005 to June 2015. The predictive value of the percentage variation of mean/maximum standard uptake value (ΔSUVmean/max), metabolic tumour volume (ΔMTV) and total lesion glycolysis (ΔTLG), estimated considering different uptake thresholds (40–50–60%), was investigated between pre- and post-RT PET. The percentage difference between gastrointestinal cancer-associated antigen (ΔGICA) levels measured at the time of PET was also considered. Log-rank test and Cox regression analysis were performed to assess the prognostic value of considered PET-derived parameters on survival outcomes. Results: The median follow-up was 13 months (range: 4–130). At univariate analysis, ΔTLG50 showed borderline significance in predicting OS ( P = 0.05) and was the most significant parameter correlated to LRFS and PFS ( P = 0.001). Median LRFS was 4 and 33 months if ΔTLG50 was below or above 35% respectively ( P = 0.0003); similarly, median PFS was 3 vs 6 months ( P = 0.0009). No significant correlation was found between PET-derived parameters and DRFS, while the ΔGICA was the only borderline significant prognostic value for this endpoint ( P = 0.05). Conclusion: PET-derived parameters predict survival in LAPC patients; in particular, ΔTLG50 is the strongest predictor. The combination of these biochemical and imaging biomarkers is promising in identifying patients at higher risk of earlier relapse.